The curse of Yig - Bishop, Zealia B. (Zealia Brown), 1897-1968; Lovecraft, H. P. (Howard Phillips), 1890-1937 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Curse of Yig" by Zealia B. Bishop and H. P. Lovecraft is a short story written in 1928 and published in 1929. It introduces Yig, a vengeful snake god who punishes those who harm serpents. When a couple settles in Oklahoma, they encounter ancient legends warning of Yig's terrible retribution. The husband's snake phobia intensifies after his wife kills rattlesnakes near their camp. Desperate rituals and mounting paranoia follow, leading to a night of horror that transforms superstition into monstrous reality. (This is an automatically generated summary.)
Wikipedia page on this work: https://en.wikipedia.org/wiki/The_Curse_of_Yig
Release date is 2023-06-04
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Short stories; Horror tales; Oklahoma -- Fiction